CRISPR/Cas9-Mediated Targeted Mutagenesis of GmUGT Enhanced Soybean Resistance Against Leaf-Chewing Insects Through Flavonoids Biosynthesis - Zhang, Yongxing; Guo, Wei; Chen, Limiao; Shen, Xinjie; Yang, Hongli; Fang, Yisheng; Ouyang, Wenqi; Mai, Sihua; Chen, Haifeng; Chen, Shuilian; Hao, Qingnan; Yuan, Songli; et al. (Frontiers in Plant Science, 2022)
Leaf-chewing insects are important pests that cause yield loss and reduce seed quality in soybeans (Glycine max). Breeding soybean varieties that are resistant to leaf-chewing insects can minimize the need for insecticide use and reduce yield loss. The marker gene for QTL-M, Glyma.07g110300 (LOC100775351) that encodes a UDP-glycosyltransferase (UGT) is the major determinant of resistance against leaf-chewing insects in soybean; it exhibits a loss of function in insect-resistant soybean germplasms. In this study, Agrobacterium-mediated transformation introduced the CRISPR/Cas9 expression vector into the soybean cultivar Tianlong No. 1 to generate Glyma.07g110300-gene mutants. We obtained two novel types of mutations, a 33-bp deletion and a single-bp insertion in the GmUGT coding region, which resulted in an enhanced resistance to Helicoverpa armigera and Spodoptera litura. Additionally, overexpressing GmUGT produced soybean varieties that were more sensitive to H. armigera and S. litura. Both mutant and overexpressing lines exhibited no obvious phenotypic changes. The difference in metabolites and gene expression suggested that GmUGT is involved in imparting resistance to leaf-chewing insects by altering the flavonoid content and expression patterns of genes related to flavonoid biosynthesis and defense. Furthermore, ectopic expression of the GmUGT gene in the ugt72b1 mutant of Arabidopsis substantially rescued the phenotype of H. armigera resistance in the atugt72b1 mutant. Our study presents a strategy for increasing resistance against leaf-chewing insects in soybean through CRISPR/Cas9-mediated targeted mutagenesis of the UGT genes.